Evaluation of Baby Corn Genotypes on Productivity and Quality traits in Bangladesh - Sarker, Mohammed Hossain; Quddus, Md. Abdul; Sattar, Md. Abdus; Karim, Mohammad Rezaul; Islam, Md. Anarul; Islam, Md. Toriqul; Ahmed, Razu; Akand, M. Matin; Hossain, Kazi Mohammad Fahid (Journal of Agricultural Studies, 2023)
Baby corn is very nutritious crop and the current demand is increasing in Bangladesh, but lacking of promising and high yielding variety. Hence, the study was conducted during the winter season of 2015-16 to evaluate twenty baby corn genotypes on the basis of quality, yield and yield contributing traits, and to find out the suitable genotype for yield maximization and quality improvement of baby corn through proper agronomic management. Twenty baby corn genotypes were planted in a randomized complete block design with three replications. As per result, the Baby Star genotype got highest cob yield with husk (11.9 t ha-1) and cob yield without husk (3.02 t ha-1) followed by Dream Sweet 3 and MSC 001. Maximum protein (11.03%) and starch content (57.03%) were recorded in Baby Star. The most total soluble solid (9.51%) was recorded in Dream Sweet-3 genotype. Baby star genotype followed by Dream Sweet 3 and MSC 001 were better than other genotypes in terms of yield attributes. Grouping of genotypes through multivariate (cluster) analysis on yield, yield attributes and quality parameters indicated that the cluster II showed higher performance among other clusters that means Baby Star, Dream Sweet-3 and MSC No.001 were better among twenty genotypes. Results suggest that Baby star followed by Dream Sweet-3 and MSC No.001 genotype can be recommended as potential baby corn genotypes for cultivation in Bangladesh and release as a variety. Some genotypes with specific features might be potential used in genetic resources for the future improvement of breeding program useful for baby corn expansion.